The Analysis of Authentic Materials Usage in Teaching English as a Second Language - Haryati Haryati; Aisyah Nurjanah; Sayudin Sayudin (Eduvest - Journal of Universal Studies, 2023)
English is an important language to master today, so English needs to be taught to children from an early age. However, in teaching English as a second language, various materials are needed that facilitate understanding, one of which is authentic material. This study aims to determine the effectiveness of using authentic material in teaching English as a second language. This research uses a descriptive method with a qualitative approach supported by documentation methods for data collection. The results showed that the use of authentic material in teaching English as a second language is very effective, considering that English needs to be taught to students from an early age. Thus, the need for various teaching methods that need to be done so that English can be understood, one of which is authentic material, because this authentic material is related to real events that occur to students, authentic material is easier for students to understand and accept.